1989
DOI: 10.1042/bj2610431
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a cysteine residue at the active site of Escherichia coli isocitrate lyase

Abstract: Escherichia coli isocitrate lyase was inactivated by iodacetate in a pseudo-first-order process. Complete inactivation was associated with the incorporation of only one carboxymethyl group per enzyme subunit. The substrate and products of the enzyme protected against inactivation, suggesting that the reactive group may be located at the active site. Isolation and sequencing of a carboxymethylated peptide showed that the modified residue was a cysteine, in the sequence Cys-Gly-His-Met-Gly-Gly-Lys. The reactivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
17
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 23 publications
3
17
0
Order By: Relevance
“…3. For the E. coli enzyme, lysine 193 and cysteine 195, both located within the first of these regions, as well as serine 319 and serine 321, situated in the third conserved domain, were identified as essential for catalysis (10,21,22,34). In accordance with these findings, the C. glutamicum enzyme possesses identical amino acids at the respective sites, indicating the importance of these amino acids in catalysis.…”
supporting
confidence: 58%
“…3. For the E. coli enzyme, lysine 193 and cysteine 195, both located within the first of these regions, as well as serine 319 and serine 321, situated in the third conserved domain, were identified as essential for catalysis (10,21,22,34). In accordance with these findings, the C. glutamicum enzyme possesses identical amino acids at the respective sites, indicating the importance of these amino acids in catalysis.…”
supporting
confidence: 58%
“…This cysteine is strictly conserved in all known ICL, consistent with its crucial role in catalysis (29,30,50,51). This cysteine was proposed to be required for deprotonation of a carboxylate of succinate during the catalytic reaction (52).…”
Section: Discussionmentioning
confidence: 58%
“…Previous studies on ICL enzymes and elucidation of the crystal structure of the enzymes with bound inhibitors (5,6,21,26,34), and similar studies of PEP mutase from Mytilus edulis (19,20), identified residues that affect the catalytic activities of these enzymes. Mutations in equivalent residues in the prpB gene were constructed, including residues C123 (the proposed active site base of ICL), D58, H125, K121, and R122 (Fig.…”
Section: Overproduction and Purification Of H 6 Prpb Proteinmentioning
confidence: 95%
“…Mechanisms of catalysis have also been proposed for the ICL proteins based on three-dimensional structures and data from active-site mutant proteins (5,6,34). Based on ICL structures with bound inhibitors and previous inhibition experiments using 3-bromopyruvate and iodoacetate, it was concluded that a cysteinyl residue was most likely the active-site residue required for isocitrate cleavage (5,6,21,26,34). It is interesting that an equivalently positioned cysteinyl residue is not conserved in PEP mutase, yet is conserved in CPEP mutase and the lyases (Fig.…”
mentioning
confidence: 99%